A location model of a trust of public firms - Feng, Xiao; Friedrich, Peter (Estonian Discussions on Economic Policy, 2014)
The decision oriented theory of the public firm (Feng, Friedrich 2013) becomes extended. The authors consider that sometimes public firms compete horizontally as well. This can be due to competition among the public owners (e.g. municipalities) considering location choices for public firms they own, or public firms competing against each other. We mention some results related to the first type of competition and we refer to how the literature on location choices under oligopolic conditions could be referred to within the framework of our basic approach. One approach by Cornes and Hartley (2001) also allows modelling the establishment of joint ventures and their location choices. The basic model of the public firm is used to provide insight into the location choices of a trust of public firms. The trust exhibits coordination at three levels via the politically-oriented decision-making body of the public owner, the trust’s headquarters and subsidiary public firms. The resulting model illustrates the interplay of different decisionmakers and the effects of the coordinating activities. The first attempts to formulate a public firm decision-making oriented location theory exist.